Effective microwave assisted synthesis of CoFe2O4@TiO2@rGO ternary nanocomposites for the synergic sonophotocatalytic degradation of tetracycline and c antibiotics. (1st May 2023) - Nimshi, R. Esther; Vijaya, J. Judith; Kennedy, L. John; Selvamani, P. Stephen; Bououdina, M.; Sophia, P. Joice
Abstract: A ternary nanocomposite CoFe2 O4 @TiO2 @rGO (CoTG) was prepared by environmentally benign and cost-efficient green microwave and sol-gel methods. The leaf extract of Pedalium murex plant was used as a reducing and stabilising agent during the microwave synthesis. The ternary nanocomposite is effectively investigated for sonophotocatalytic degradation of tetracycline and ciprofloxacin antibiotics in the presence of visible light and ultrasonic irradiation. The XRD, FTIR and EDX results corroborate the pure phase of CoFe2 O4 /TiO2 /rGO nanocomposite. The spherical TiO2 and CoFe2 O4 nanoparticles are well impregnated into the sheets of rGO as evidenced by TEM analysis. The CoFe2 O4 /TiO2 /rGO nanocomposite effective visible light active bandgap is elucidated by DRS analysis. The CoTG nanocomposite shows a high efficiency of 92% and 84% degradation of Tetracycline (20 mg/L) and Ciprofloxacin (10 mg/L) within a short duration during the sonophotocatalytic degradation process. As stated by the kinetics analysis, the degrading process complies a pseudo-first order reaction with the following rate constant: Ksonophotocatalytic > Kphotocatalytic > Ksonocatalytic . CIP and TC antibiotics both achieve the high synergic value of 1.375 during degradation. Due to the continuous production of OH and O2 radicals, free electrons actively participate in the degradation process, thereby creating synergistic effects. Using ternary CoTG nanocomposite, this study demonstrates an enhanced approach to antibiotics' degradation toward environmental remediation and protection.